Interface design considerations for elderly friendly internet banking / Mohamad Redzuan Harris Mohamad Fadzil - Mohamad Fadzil, Mohamad Redzuan Harris (2014)
Online banking is a necessity in today's modern society. With the advent of information technology, banking transactions are now faster, easier and more convenient for internet users. Due to its strong foundation and huge potential, online banking has now become an important asset and vital element to a banking institution. However, despite of its fast emergence and vast acceptance among internet users, most of the interface designs for online banking website was not designed and developed to support all types of users where it can be seen to only target younger demographics. While for the older people, their usability consideration were ignored and left behind. This research seek to find the interface design considerations to produce Elderly Friendly Internet Banking by providing few recommendations based on current usability issues and user preferences gathered using Technology Probe.